Law Enforcement Intelligence Operations: Reformation of the Legislation of Kazakhstan in the Context of International Changes - SHALKAROVA, Irina; USHUROV, Camille (Journal of Advanced Research in Law and Economics, 2019)
This article analyzes the trends in the development of legislation on law enforcement intelligence operations in Kazakhstan. The reforms that have affected the criminal proceedings in Kazakhstan in recent years have significantly changed their ratio with law enforcement intelligence operations. Accordingly, the prospects for their legislative regulation in Kazakhstan currently require scientific analysis taking into account the changes in the law enforcement sphere. The emergence of the institute of criminal intelligence and surveillance operations in the criminal proceedings of Kazakhstan and the adoption of an independent law regulating counterintelligence operations entail a reduction in the number of tasks related to law enforcement intelligence operations and give reasons to doubt the further need for the Law on Law Enforcement Intelligence Operations of Kazakhstan and consider its possible abolition. The authors assess the innovations related to the artificial division of law enforcement intelligence operations into two types (law enforcement intelligence operations and criminal intelligence and surveillance operations). It is noted that they have led to the emergence of new problems in the theory of criminal proceedings and in the law enforcement practice. The work determines the place of the main tool for law enforcement intelligence operations within and beyond the criminal proceedings. This research paper demonstrates the similarities and differences in the goals, objectives, and role in the proving process of these almost identical actions of the criminal prosecution authorities – law enforcement intelligence operations and criminal intelligence and surveillance operations. As a result of a comparative and legal analysis of the criminal procedure and law enforcement intelligence legislation of the United States and Germany, as well as a study of the theoretical views of various researchers, the main trends in the normative regulation of the criminal intelligence and surveillance methods of operation of the law-enforcement authorities in Kazakhstan were identified. The authors substantiate the need to preserve the Law on Law Enforcement Intelligence Operations of Kazakhstan and further improve the law enforcement and intelligence legislation. To support this position, the authors note that the criminal investigation and tracing of missing persons, crime prevention and verification work, which are important areas of law enforcement intelligence operations, are not regulated by the criminal proceedings and the counterintelligence legislation. Thus, they require regulation by a separate legislative institution in the field of law enforcement. In addition, a number of facts are given indicating that there is potential for expanding the scope of the Law on Law Enforcement Intelligence Operations of Kazakhstan